Financial intermediation and efficient risk sharing in two-period lived OLG models - Paul Ritschel; Jan Wenzelburger (Economic Theory Bulletin, 2024)
This article investigates a two-period lived overlapping-generations (OLG) model that incorporates financial intermediation. A risk-neutral bank offers loan and deposit contracts that insure risk-averse agents against idiosyncratic income shocks. Agents prefer financial intermediation to capital markets if it provides efficient risk sharing. The analysis demonstrates that in any two-period lived OLG model in which productive capital is increasing in investment levels, financial intermediation, when implemented for the purpose of efficient risk sharing, cannot instigate business cycles or complex dynamics. The resulting dynamics is monotonic and qualitatively indistinguishable from the dynamics of the classical OLG model by Diamond (Am Econ Rev 55(5):1126–1150, 1965). Business cycles may only occur if banks offer inefficient contracts. Efficient contracts will, in general, not induce dynamically efficient growth paths.
Keywords: D53; E32; E44; G21; O41; 330; Financial intermediation; Overlapping generations; Risk sharing; Business cycles; Loan contracts